2005
DOI: 10.4049/jimmunol.174.7.4407
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Regulatory T Cells in HIV Infection Is Associated with Immune Activation

Abstract: Immune activation during chronic HIV infection is a strong clinical predictor of death and may mediate CD4+ T cell depletion. Regulatory T cells (Tregs) are CD4+CD25brightCD62Lhigh cells that actively down-regulate immune responses. We asked whether loss of Tregs during HIV infection mediates immune activation in a cross-sectional study of 81 HIV-positive Ugandan volunteers. We found that Treg number is strongly correlated with both CD4+ and CD8+ T cell activation. In multivariate modeling, this relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
299
4
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(327 citation statements)
references
References 61 publications
16
299
4
8
Order By: Relevance
“…In the initial phase, higher Treg activity induces a paradoxical effect of stabilized CD4 + levels by reducing CD8 + T activity (Kinter et al 2004, Eggena et al 2005. Therefore, the progressive reduction in Tregs results in an increased Th2 CD4 + T lymphocyte response to environmental allergens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial phase, higher Treg activity induces a paradoxical effect of stabilized CD4 + levels by reducing CD8 + T activity (Kinter et al 2004, Eggena et al 2005. Therefore, the progressive reduction in Tregs results in an increased Th2 CD4 + T lymphocyte response to environmental allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this contradictory effect has been attributed to functional and quantitative alterations in regulatory T cells (Kinter et al 2004, Eggena et al 2005). These observations suggest that immunological alterations secondary to HIV infection alter the normal allergy control mechanisms, thus permitting an increase in the clinical expression of allergic diseases (Bacot et al 1997).…”
mentioning
confidence: 99%
“…However, the circulating frequency of CD4 + Treg cells has not been found to show any correlation with the magnitude of HIV‐specific T‐cell responses,276, 277, 278 leaving the contribution of CD4 + Treg cells to regulation of virus‐specific T‐cell responses in HIV‐infected individuals unclear. Their role in suppressing immune activation is also uncertain.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
“…Thus, several groups have shown that Tregs numbers are either decreased [8,96,97,104,105] or increased [91,95,100,101] in HIV-1 infection. A clearer understanding of Tregs in disease progression has come to light with the use of monkey models of HIV infection.…”
Section: Relative Levels Of Foxp3 and Treg During Hiv-1 Infection Andmentioning
confidence: 99%
“…Epple et al [91] Montes et al [92] Mozos et al [93] Lim et al [94] Andersson et al [95] Epple et al [91] Nilsson et al [100] ↓ Oswald-Richter et al [8] Andersson et al [95] Apoil et al [96] Eggena et al [97]; Baker et al [98] Mozos et al [93] Treg levels a …”
Section: Treg Levels Amentioning
confidence: 99%